Proposed Marketing Strategy for TELKOM FLEXI to Compete with GSM Operators - Mardiansyah, Marshal; Desiana, Krisnati; Nasution, Reza Ashari (The Indonesian Journal of Business Administration, 2013)
In Indonesian telecommunication industry, market penetration of FWA (Fixed Wireless Access) based is still about 12% of the total population size. But the market penetration of GSM (Global System for Mobile Communications) based in cellular telecommunication industry has reach 82%. Therefore when the FWA operators in Indonesia want to expand their market, they will have to compete with GSM operators. As market leader of FWA license in Indonesia, it is time for Flexi for extending their network and also targeting new market that were not their target market so far, GSM users. Flexi is a voice and data telecommunications service based on wireless CDMA (Code Division Multiple Access) 2000-1x technology. This is a limited mobility service, meaning that, unlike cellular subscribers, Flexi customers can only use the service within a particular area code. Charges are based on residential telephone (PSTN TELKOM) tariffs. Flexi offers three basic services: voice, SMS and high speed data. This study explores the problem of Flexi In competing with GSM operators using several analyses. The relevant external environment factor that may influence telecommunication industry and Flexi's business is analyzed with Porter’s Five Forces model. The company’s resources, capabilities and core competencies are determined to identify what company can and cannot do. Then the segmentation, targeting and positioning of Flexi will be analyzed. The perception, motivation, and buying decision of customer is also explored to get insight about why the customers want or don't want to use CDMA Flexi. Finally, the existing marketing strategy (marketing mix) of Flexi is examined to describe the symptoms and errors within it, in order to formulate the root causes. No firm positioning statement, doesn’t actively provide handset for its target market, ineffective promotional activities, and low of product knowledge are the root causes of Flexi's low acceptance in the market. Therefore, to overcome those root causes, then formulate a more firm positioning statement and tagline to be more suitable with Flexi's target market, improving product weaknesses, and use a community as marketing campaign media are what Flexi have to do to have a more effective marketing effort. The management should develop promotion strategy which is composed of six elements: advertising, personal selling, sales promotion, direct marketing, internet marketing, and public relations.  Keyword: Marketing Strategy, Marketing Mix, CDMA, GSM